Rethinking Readings About the Past of School and Education Between Worlds - Batista da Silva, Vivian; Gonçalves Vidal, Diana; Godinho Lima, Ana Laura; Bontempi Jr., Bruno (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
This paper introduces the book Rethinking Centre-Periphery Assumptions in the History of Education: Exchanges Among Brazil, USA, and Europe, recently published by Routledge, as a result of the FAPESP Thematic Project No. 2018/26699–4 entitled Knowledges and practices at the borders: for a transnational history of education (1810–). It is structured in two parts. The first part evinces the exchanges established between Brazil and the USA, with a focus on the circulation of subjects and pedagogical models. The narrative starts in 1884 with the trip of Maria Guilhermina Loureiro to the USA and extending to 1960 with the connections between New Education and Modern Architecture. Along the way, it deals with the education debates carried out in the state of São Paulo around the writing of the report Education in the State of São Paulo (1903), and the sojourn of Brazilian educators in the Columbia University Teachers College (NY) from 1920 to 1960. In the second part, the circle is widened, incorporating the exchanges with Europe, particularly with France, England, and Portugal. Here we conduct analyses about the circulation of artifacts such as desks, parietal charts, and school manuals, as well as of models of representation such as Pictorialism photography.